Boehmians of Lp - growth. Issue 8 (2nd August 2016) - Nemzer, D.
ABSTRACT: Spaces of Boehmians having L p -growth ( 1 ≤ p ≤ ∞ ) are constructed and studied. For 1 ≤ p ≤ 2, the Fourier transform is defined and properties are established. An inversion formula and an uncertainty principle are given for Boehmians.